Development of RB1 mutation detection method based on mRNA - Nhung, Vũ Phương; Quỳnh, Lê Thúy; Tôn, Nguyễn Đăng; Xuân, Nguyễn Thị; Hà, Nguyễn Hải (Vietnam Journal of Biotechnology, 2016)
Retinoblastoma (Rb) is a malignant tumor of the retina, occurring usually in children before age five. The heritable form acounting for about 40% of Rb making genetic analysis of RB1 gene is a important part of disease management. In previous study, we have successfully employed a method of direct sequencing for RB1 mutation screening from genomic DNA. However, given the large size of this gene and no reported mutation hotspots, the testing can be costly and time consuming method. To overcome this problem, we have developed a method to detect mutation from RB1 mRNA. Total RNA was isolated from blood leukocytes of a healthy individual and a Rb patient, cDNA was subsequently synthesized using reverse-transcriptase PCR. Whole cDNA of RB1 was amplified using six specific primer pairs and sequenced by Sanger method. The PCR products from healthy individual were showed as six specific bands on the agarose gel and could be used as the standard pattern of the normally spilced transcripts. Those of PCR products were sequenced successfuly and data can be aligned with the reference sequence of RB1 cDNA on the Genebanhk to identify nucleotide variants.  We also identified an upnormal splicing of RB1 gene in the Rb patient haboring a c. G1960>C mutation at the end of the exon 19 by amplification of  the RB1 cDNA fragments. Hence using RB1 mRNA test can reveal not only the silent/pathogenic mutations in the coding region of RB1, but also mutations that affect the normal spilcing of RB1 mRNA. This method reduces cost and time, can be used as the first step of RB1 analysis in Rb patients.